Measures of Dogs' Inhibitory Control Abilities Do Not Correlate across Tasks - Brucks, Désirée; Marshall-Pescini, Sarah; Wallis, Lisa Jessica; Huber, Ludwig; Range, Friederike (Frontiers in Psychology, 2017)
Inhibitory control, the ability to overcome prepotent but ineffective behaviors, has been studied extensively across species, revealing the involvement of this ability in many different aspects of life. While various different paradigms have been created in order to measure inhibitory control, only a limited number of studies have investigated whether such measurements indeed evaluate the same underlying mechanism, especially in non-human animals. In humans, inhibitory control is a complex construct composed of distinct behavioral processes rather than of a single unified measure. In the current study, we aimed to investigate the validity of inhibitory control paradigms in dogs. Sixty-seven dogs were tested in a battery consisting of frequently used inhibitory control tests. Additionally, dog owners were asked to complete an impulsivity questionnaire about their dog. No correlation of dogs’ performance across tasks was found. In order to understand whether there are some underlying behavioral aspects explaining dogs’ performance across tests, we performed principle component analyses. Results revealed that three components (persistency, compulsivity and decision speed) explained the variation across tasks. The questionnaire and dogs’ individual characteristics (i.e. age and sex) provided only limited information for the derived components. Overall, results suggest that no unique measurement for inhibitory control exists in dogs, but tests rather measure different aspects of this ability. Considering the context-specificity of inhibitory control in dogs and most probably also in other non-human animals, extreme caution is needed when making conclusions about inhibitory control abilities based on a single test.